Classification of a Hypervirulent Aeromonas hydrophila Pathotype Responsible for Epidemic Outbreaks in Warm-Water Fishes - Rasmussen-Ivey, Cody R.; Hossain, Mohammad J.; Odom, Sara E.; Terhune, Jeffery S.; Hemstreet, William G.; Shoemaker, Craig A.; Zhang, Dunhua; Xu, De-Hai; Griffin, Matt J.; Liu, Yong-Jie; Figueras, Maria J.; Santos, Scott R.; et al. (Frontiers in Microbiology, 2016)
Lineages of hypervirulent Aeromonas hydrophila (vAh) are the cause of persistent outbreaks of motile Aeromonas septicemia in warm-water fishes worldwide. Over the last decade, this virulent lineage of A. hydrophila has resulted in annual losses of millions of tons of farmed carp and catfish in the People's Republic of China and the United States (US). Multiple lines of evidence indicate US catfish and Asian carp isolates of A. hydrophila affiliated with sequence type 251 (ST251) share a recent common ancestor. To address the genomic context for the putative intercontinental transfer and subsequent geographic spread of this pathogen, we conducted a core genome phylogenetic analysis on 61 Aeromonas spp. genomes, of which 40 were affiliated with A. hydrophila, with 26 identified as epidemic strains. Phylogenetic analyses indicate all ST251 strains form a coherent lineage affiliated with A. hydrophila. Within this lineage, conserved genetic loci unique to A. hydrophila were identified, with some genes present in consistently higher copy numbers than in non-epidemic A. hydrophila isolates. In addition, results from analyses of representative ST251 isolates support the conclusion that multiple lineages are present within US vAh isolated from Mississippi, whereas vAh isolated from Alabama appear clonal. This is the first report of genomic heterogeneity within US vAh isolates, with some Mississippi isolates showing closer affiliation with the Asian grass carp isolate ZC1 than other vAh isolated in the US. To evaluate the biological significance of the identified heterogeneity, comparative disease challenges were conducted with representatives of different vAh genotypes. These studies revealed that isolate ZC1 yielded significantly lower mortality in channel catfish, relative to Alabama and Mississippi vAh isolates. Like other Asian vAh isolates, the ZC1 lineage contains all core genes for a complete type VI secretion system (T6SS). In contrast, more virulent US isolates retain only remnants of the T6SS (clpB, hcp, vgrG, and vasH) which may have functional implications. Collectively, these results characterize a hypervirulent A. hydrophila pathotype that affects farmed fish on multiple continents.